Peningkatan Pemahaman Konsep Ciri-Ciri Khusus Hewan dengan Metode Take and Give di Kelas III SDN Sananwetan 2 Kota Blitar - Ariadi (Civiliza Publishing, 2022)
To gain a comprehensive understanding of Indonesian language learning strategies and their effectiveness in achieving learning objectives, this research literature review will focus on (1) language learning, (2) Indonesian language learning strategies, including Indonesian language learning methods and techniques, and (3) learning outcomes. This study aims to improve the learning outcomes of third grade Indonesian at SD Negeri Sananwetan 2 Blitar City after the application of the Take and Give method. This type of research is classroom action research which consists of two cycles. The research subjects were 28 third grade students. Learning outcomes were collected by the test method. The data collected were analyzed by quantitative descriptive. The results of the study showed an increase in Indonesian language learning outcomes through the application of the Take and Give method for third grade students. It can be seen from the average percentage of learning outcomes obtained before group action reached 43% and individuals reached 36%. The Take and Give learning method is a learning method that has steps, which require students to be able to understand the subject matter given by the teacher and their peers.